2014
DOI: 10.1007/s00432-014-1829-6
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of targeted therapies in the standard of care for metastatic colorectal cancer patients in a German cancer center: the more the better?!

Abstract: Our results indicate successful allocation of the current mCRC treatment according to the Kras status. Differences in OS of wt Kras patients indicated the further need for randomized trials to define the potential benefit of sequential therapy with EGFR inhibition in first-line therapy followed by VEGFR inhibition vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Second, our data indicate that tumor cell intravasation could be sensitive even to moderate diminishment of EGFR-dependent production of VEGF and IL-8 proteins, IL-8–dependent neutrophil influx, and ensuing delivery of neutrophil MMP-9 releasing matrix-bound VEGF. The dependence of intravasation-sustaining intratumoral vessels on VEGF that regulates their permeability and integrity could be reflected in increased benefits of anti-EGFR therapies combined with anti-VEGF agents, a combinatorial approach currently used in clinic, albeit mainly for late-stage cancers [49] , [69] , [70] , [71] . Furthermore, our newly established mechanism suggests that additional beneficiary effects may come from combining EGFR-targeted therapy with anti–IL-8 and/or anti-inflammatory drugs [72] .…”
Section: Discussionmentioning
confidence: 99%
“…Second, our data indicate that tumor cell intravasation could be sensitive even to moderate diminishment of EGFR-dependent production of VEGF and IL-8 proteins, IL-8–dependent neutrophil influx, and ensuing delivery of neutrophil MMP-9 releasing matrix-bound VEGF. The dependence of intravasation-sustaining intratumoral vessels on VEGF that regulates their permeability and integrity could be reflected in increased benefits of anti-EGFR therapies combined with anti-VEGF agents, a combinatorial approach currently used in clinic, albeit mainly for late-stage cancers [49] , [69] , [70] , [71] . Furthermore, our newly established mechanism suggests that additional beneficiary effects may come from combining EGFR-targeted therapy with anti–IL-8 and/or anti-inflammatory drugs [72] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings from preclinical [19][20][21]28] and retrospective clinical studies [18] collectively suggest that prolonged treatment with anti-EGFR antibody shifts the cancer cells toward a less EGFR-dependent phenotype and more VEGF-dependent angiogenesis; therefore, the use of an anti-EGFR antibody before bevacizumab appears to be a beneficial sequence for a targeted molecular therapy approach.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent retrospective analysis of the sequential use of bevacizumab and anti-EGFR antibody found that the prior use of bevacizumab had an ad- verse effect on the subsequent activity of the anti-EGFR antibody [25][26][27] . On the other hand, the prior use of the anti-EGFR antibody was suggested to elicit some biological changes to the tumors that made them more sensitive to subsequent bevacizumab-containing therapy [18,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, a recent retrospective analysis of 103 patients noted a trend towards improved OS in patients receiving first-line EGFR inhibitors and second-line VEGF inhibitors, compared with patients receiving first-line VEGF inhibitors and second-line EGFR inhibitors [78]. Similarly, a prior study involving 58 patients with mCRC reported that previous exposure to VEGF inhibitors decreased the efficacy of subsequent EGFR inhibitor-based therapy [79].…”
Section: Z a Wainberg And A Drakakimentioning
confidence: 84%